Reconsidering central bank independence - Du Plessis, Stan 1972-; Freytag, Andreas 1958-; Van Lill, Dawie 1986- (Cambridge University Press, 2024)
Central bank independence has become one of the most widely accepted tenets of modern monetary policy. According to this view, the main role of independent central banks is to maintain price stability through the adjustment of short-term interest rates. Reconsidering Central Bank Independence argues that the global financial crisis has undermined confidence in this view as central banks increasingly have to address concerns other than price stability, such as financial stability, the need for output recovery and other broader policy goals. Large balance-sheet expansion by central banks followed the global financial crisis, which overlapped considerably with the financial policy of their respective governments. Exploring the consequences of this shift to a more diverse set of policy challenges, this book calls for a return to the consensus role for central banks and analyses what this might mean for their future independence.
Keywords: Banks and banking, Central